Politics, pauperism and power in late nineteenth-century Ireland. - Crossman, Virginia (Manchester University Press, 2017)
This is a study of the nature and operation of the Irish poor law system in the post-famine period. It traces the expansion of the system to encompass a wide range of welfare services, and explains the ideological and political context in which expansion took place. The only local government bodies in rural areas to include elected members, poor law boards provided many Irish nationalists with their first experience of administrative power. As the influence of the nationalist guardians in the south and west grew, so the character of poor law administration in these areas began to change. Cross.